POLICE RECONSTRUCTION POLICY AND LAW IN THE IMPLEMENTATION OF ATTORNEY RESTORATIVE JUSTICE EMBEZZLEMENT BASED CRIME LAW PROGRESSIVE - Sulistyowati sulistyowati (UNISSULA, 2017)
The aim of this study is to determine and assess the legal policy in the Police and the Prosecutor in the application of restorative justice criminal offense of embezzlement today, to know and study the the obstacles of legal policy in the Police and the Prosecutor in the application of restorative justice acts criminal embezzlement based on Progressive Law .This research is descriptive analytic research, which means the results of this study seeks to provide a thorough and in-depth description of a situation, fact or phenomenon. Approach method used in this study was empirical juridical approach or Socio - Legal Research. Analysis data used in this research was a qualitative descriptive data analysis.Results of this study are (1) The policy of law on the Police and the Prosecutor in the application of restorative justice criminal offense of embezzlement is for the investigation of the offenses of embezzlement. The investigators still examine the perpetrators, victims and witnesses, as well as what happens at the level of the prosecution attorney. The attorneys as a public prosecutor still proceed with the prosecution in accordance with the criminal procedure. Justice system if the parties so good Perpetrators, agreed to make peace and do not want to continue the case to the next process, the Investigator Police will apply discretion by allowing the case file was hanging in the sense of not issued Warrant Termination of Investigation but did not proceed to the extent prosecution. Also at the level of prosecution, as the Attorney General Prosecutor not issued Cessation prosecution but also does not proceed bestow the file to the Court; (2) Factors to be obstacles in the implementation of legal policies Police and the Attorney General in the implementation of restorative justice criminal offense of embezzlement at this time.